Estudo da síntese in situ de nanopartículas e filmes finos de óxido de zinco dopado com alumínio por rota hidrotermal convencional e assistida por micro-ondas - Serrão, Fernanda Thamiles de Jesus (Universidade Federal de São Carlos, 2023)
Zinc oxide (ZnO) is one of the most interesting materials due to its wide range of applications in various optoelectronic devices, such as light-emitting diodes, photodetectors, sensors, UV absorbers, solar cells, among others. However, ZnO's low electrical conductivity limits several of its applications, despite being a promising material for optoelectronic devices due to confinement effects. One way to overcome this problem is by doping, substituting Zn2+ ions with group III ions (B3+, Al3+, Ga3+, and In3+), which can promote electrons to the conduction band and improve the optical, thermal, magnetic, and electrical properties of ZnO. Among these dopants, Al3+ is the most commonly used due to its small ionic radius and low production cost. In this context, this study aims to synthesize and analyze the synthesis parameters of Al-doped ZnO nanoparticles (AZO) by using hydrothermal routes under conventional heating and assisted by microwave irradiation, in an aqueous medium. The materials and synthesis parameters will be characterized using X-ray diffraction (XRD), diffuse reflectance spectroscopy (DRS), Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, transmission electron microscopy (TEM). For the syntheses deposited on glass substrates, optical microscopy (OM) and scanning electron microscopy (SEM) were performed.
Study of in situ synthesis of aluminum-doped zinc oxide nanoparticles and thin films by conventional hydrothermal route and microwave-assisted method
Keywords: Nanopartícula; Síntese; AZO; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS